Coaching Class Treding Saham LQ-45 untuk Mahasiswa Universitas Bumigora - Ahmad Zuli Amrullah; Gilang Primajati; Siti Soraya (LPPM Universitas Bumigora, 2021)
The main problem faced by these partners is people's understanding of the capital market, both technical and non-technical. For technical problems, the community does not understand how to start stock treding in the capital market regarding the application, methods and tools. Meanwhile, the non-technical obstacles faced are the problem of knowledge about treding how to get good benefits, how to reduce risks, and what types of investment should be made in investing. The solution and target to be achieved is to increase the ability and interest of the community, especially students, to start investing in the capital market with various application tools. The method used in this service is by means of coaching classes accompanied by simulations in the framework of learning development and service learning on stock trading tools affiliated with the Indonesian stock exchange. At the time the service began with learning the basics of the capital market to students then continued with real simulations using a virtual account with a 30 minute delay from real time data from the Indonesia Stock Exchange. The result obtained is to open horizons of thought that stock trading is not difficult, it can be done by anyone. In the process, in virtual account, many students managed to get a positive return income.